Absorption and phase decoupling in transport of intensity diffraction tomography. (September 2022) - Bai, Zhidong; Chen, Qian; Ullah, Habib; Lu, Linpeng; Zhou, Ning; Zhou, Shun; Li, Jiaji; Zuo, Chao
Highlights: We have presented a validated transport of intensity diffraction tomography technique with partially coherent illumination for imaging the absorption and refractive index of weakly scattering samples in 3D dimensions. Solving the problem of refractive index and absorption couplings in the physical model of scattering potential without the pure phase approximation or linearized absorption. Based on a global non-iterative decoupled reconstruction algorithm, the object's phase and absorption components can be decoupled in TIDT from the two intensity measurement data sets captured on a standard brightfield microscope. The proposed technique is fully compatible with ubiquitous bright-field microscopy hardware, which opens up a new pathway for investigating the structural diversity of biological cells at the subcellular level. Abstract: Here we report a valid reconstruction approach to decouple the phase and absorption components of complex refractive index in the transport of intensity diffraction tomography (TIDT) microscopy. Within the existed diffraction tomographic reconstruction framework, the objects refractive index (RI) and absorption components are usually intertwined with each other in the scattering field, complicating the complex refractive index reconstruction process. With the closed-form deconvolution solution and two intensity image datasets captured through focus, we realize the decoupling of the RI part of the specimens and the absorption part in TIDT without pure phase approximation or linearized weak absorption. The difference between the RI and absorption parts of the complex refractive index reconstruction reveals the optical properties of the different components of the object. Simulation and experiments are both performed to validate our decoupling approach based on the simulated 3D resolution target, human breast cancer cell lines MCF-7 and Thalassiosira diatom. The results of the simulations and experiments suggest that the proposed approach is successful and effective for investigating the structural diversity of biological cells at the subcellular level.